Dampak TGT (Teams Games Tournament) terhadap Hasil Belajar Kognitif Siswa pada Konsep Sistem Ekskresi Manusia : [The Impact of TGT (Teams Games Tournament) on Students' Cognitive Learning Outcomes on the Concept of the Human Excretory System] - Rizki Triandari; Yules Gustaf Messa; Maulana Iskak (Universitas Pelita Harapan, 2025)
Education is a deliberate effort to help children become mature and take responsibility for themselves, their families, communities, nations, and countries. Many schools in Indonesia still use conventional teaching methods that tend to make students passive and uninvolved in the learning process. Therefore, it is necessary to change the teaching method to a more innovative and interactive one to increase student engagement and improve learning outcomes. This study aims to investigate the effect of the cooperative learning model, specifically the Teams Games Tournament (TGT) type, on student learning outcomes in eighth-grade students on the human excretory system. The method used in this study is the pretest and post-test method, which was given in the form of questions to 64 students of class 8.1 and 8.2 at SMP Kristen Tiara Kasih in West Jakarta. The results of this study indicate that the TGT model has a significant effect on student learning outcomes. This study is expected to contribute to the development of more effective and innovative teaching methods to help students achieve optimal results.